1993
DOI: 10.1172/jci116365
|View full text |Cite
|
Sign up to set email alerts
|

Fluid and electrolyte transport by cultured human airway epithelia.

Abstract: An understanding of the fluid and electrolyte transport properties of any epithelium requires knowledge of the direction, rate, and regulation of fluid transport and the composition of the fluid. Although human airway epithelia likely play a key role in controlling the quantity and composition of the respiratory tract fluid, evidence for such a role is not available. To obtain such knowledge, we measured fluid and electrolyte transport by cultured human nasal epithelia. Under basal conditions we found that epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 52 publications
6
55
1
Order By: Relevance
“…This was confirmed by Krouse et al [33] in the Ussing chamber with the addition that there existed a H-K ATPase to help neutralize some of the bicarbonate which was secreted. Such a mechanism had been previously reported by Smith and Welsh [27] in airway cells and again by Coakley et al [29] in primary airway cell cultures. In the same year Wu et al [94] published a paper showing an inwardly rectifying potassium channel (Kir4.2) in the apical membrane of Calu-3 cells and also in the apical membrane of freshly dissected airway submucosal glands.…”
Section: Mike Knowles and Richard Boucher University Of North Carolisupporting
confidence: 69%
See 2 more Smart Citations
“…This was confirmed by Krouse et al [33] in the Ussing chamber with the addition that there existed a H-K ATPase to help neutralize some of the bicarbonate which was secreted. Such a mechanism had been previously reported by Smith and Welsh [27] in airway cells and again by Coakley et al [29] in primary airway cell cultures. In the same year Wu et al [94] published a paper showing an inwardly rectifying potassium channel (Kir4.2) in the apical membrane of Calu-3 cells and also in the apical membrane of freshly dissected airway submucosal glands.…”
Section: Mike Knowles and Richard Boucher University Of North Carolisupporting
confidence: 69%
“…The same thing happened when the calcium inside the cells was increased except a different set of anion channels were opened and bicarbonate can pass through in both normal and CF tissues. The following year Smith and Welsh [27] published a paper studying electrolyte transport in cultured airway epithelia cells. It was found that both normal and CF tissue secreted H+ in exchange for K+.…”
Section: The Lungsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ϫ and HCO 3 Ϫ is important in the airway epithelium to control electrolyte and fluid secretion and to regulate pH (1)(2)(3). In particular, Cl Ϫ transport is recognized as one of the important factors in the regulation of airway surface hydration and therefore in mucociliary clearance (4).…”
Section: T Ransport Of Anions Like CLmentioning
confidence: 99%
“…Therefore we used a novel targeting strategy to introduce the A\F508 mutation into the mouse CFTR gene (13) . Murine CFTR is 78% identical to human CFTR (14,15) and it contains a phenylalanine at residue 508 flanked by 28 amino acids identical to those in human CFTR. The goal of this work was to generate animals homozygous for the AF508 mutation (L/F/AF mice).…”
Section: Introductionmentioning
confidence: 99%